Uwarunkowania subiektywnej oceny sytuacji ekonomicznej indywidualnych gospodarstw rolnych w opinii ich właścicieli - Krot, Katarzyna; Glińska, Ewa (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2014)
Subjective assessment of the economic situation of the farm is an important research issue, since it affects the quality of farmers’ life and their decisions connected with agriculture production. Therefore, the aim of this paper is to identify the socio-economic determinants of subjective assessment of the economic situation of individual farms, based on surveys carried out on a sample of nearly 400 farmers in Podlaskie region. In order to identify factors explaining the level of subjective assessment of economic situation of farms multiple regression model was used. The results indicate that the subjective assessment of the economic situation and the condition of farms include: (a) structural factors such as the annual income from the farm and its size, (b) individual factors: intention to provide the farm to children what expresses the commitment and dedication of the farmer to his farm, and (c) the degree of modern methods used in farm production.